A Comprehensive Lexico-Syntactic Analysis Of Stylistic Devices In Ernest Hemingway’s «The Old Man And The Sea» (Texas Journal of Engineering and Technology, 2025)
This article offers a thorough lexico-syntactical examination of Ernest Hemingway's use of stylistic elements in «The Old Man and the Sea» . The study focuses on Hemingway's unique minimalist style and examines how the rhythm and tone of the story are improved by his use of syntactical devices like parataxis, repetition, and polysyndeton. The lexical analysis emphasizes Hemingway's purposeful use of monosyllabic words and straightforward, tangible terminology, which adds to the setting's and characters' realism.